The use of filter paper as a transport device for serology of Pasteurella multocida infection : Analysis and comparison ofprotein composition of filter paper extract and serum - Natalia, Lily; Priadi, Adin (Indonesian Animal Sciences Society, 1998)
Two methods for collecting blood specimens for measuring antibody to Pasteurella multocida were compared. Blood was collected on filter-paper strips, air-dried and stored at 4Â°C along with paired samples collected by venepumeture . Analysis using sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) showed that the protein composition of filter paper extract and serum was similar. Both samples had common proteins of 67, 52-58 and 27 kDa. However, there are two proteins bands of 14 and 30 kDa that were only found in, filter-paper extract. Westernblot analysis also showed that samples from both sampling techniques reacted to P. multocida proteins of 43 kDa. Samples from experimental and field animals were also collected by the two techniques and assayed by enzyme-linked immunosorbent assay (ELISA) for P. multocida antibodies . The agreement between samples from experimental animals and the field using ELISA was analyzed . Samples from experimental animals, showed a very high correlation (r = 0.931) in ELISA results among samples collected by the two techniques. However, the correlation was lower (r = 0.799) in samples collected from the field. Cost analysis showed that filter-paper collection technique was 100 times more economical compared to venepuncture technique. It was concluded that eluates of whole blood dried on filter paper can be used as an alternative to sera in ELISA for measuring antibodies to P. multocida. Â Key words : Pasteurella multocida, serological tests, filter paper